Hierarchical porous sodium electric hard carbon negative electrode material and preparation method thereof
By preparing a graded pore sodium electrohard carbon negative electrode material with micropores, mesoporous, carbon nanotubes and clad structures, the problem of side reactions of hard carbon materials during the first charging and discharging process in sodium ion batteries is solved, and the first-effect and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411818065.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing hard carbon materials are prone to side reactions with the electrolyte during the first charging and discharging process in sodium ion batteries, resulting in a decrease in the first effect of the battery and a high specific surface area to increase the degradation of the material, affecting the battery's rate performance.
By preparing a graded pore sodium electrohard carbon negative electrode material with micropores, mesoporous, carbon nanotubes and clad structures, the ion transmission path and electron conduction are optimized, and the occurrence of side reactions is reduced.
Significantly improve the first-effect and rate performance of sodium ion batteries, and reduce the occurrence of side reactions by optimizing ion transmission path and electron conduction.
Smart Images

Figure BDA0005182378800000191 
Figure BDA0005182378800000201 
Figure BDA0005182378800000211
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery negative electrode materials, and in particular relates to a graded pore sodium electric hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] As an electrode material, hard carbon is widely used in the field of electrochemical energy storage, especially in sodium-ion batteries. Traditional hard carbon materials have significant advantages in ion diffusion kinetics and platform sodium storage due to their rich microporous structure, which is far superior to lithium-ion graphite. However, the pore structure of hard carbon materials has a profound impact on their electrochemical properties. The opening and closing of micropores directly affects the specific surface area and platform sodium storage capacity of the material: increasing closed pores can increase the platform sodium storage capacity, while increasing open pores can increase the specific surface area and ion diffusion kinetics.
[0003] In order to improve the kinetic properties of hard carbon materials, the mainstream method is to introduce more pore structures by improving the pore structure. However, microporous structures are usually introduced, which will significantly increase the specific surface area of hard carbon materials. However, hard carbon materials with high specific surface area are prone to side reactions with the electrolyte during the first charge and discharge process, resulting in a decrease in the initial efficiency of the battery. In addition, the high specific surface area will also increase the contact area between the material and the electrolyte, accelerate the degradation of the material, and affect the battery rate performance.
[0004] Therefore, there is an urgent need for a hierarchical pore sodium electric hard carbon negative electrode material and a preparation method thereof to solve the deficiencies of the existing technical problems. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a graded porosity sodium electric hard carbon negative electrode material and a preparation method thereof. The graded porosity sodium electric hard carbon negative electrode material prepared by the preparation method has micropores, mesopores, carbon nanotubes and coating layer structures, which can optimize the ion transmission path and electron conduction and reduce the occurrence of side reactions, thereby significantly improving the first efficiency and rate performance of sodium ion batteries.
[0006] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a hierarchical pore sodium electric hard carbon negative electrode material, the steps comprising:
[0007] S1, mixing a hard carbon precursor material and a pore-forming agent 1 and then pre-carbonizing at a low temperature to obtain a first composite material;
[0008] S2, crushing the first composite material to obtain a fine powder;
[0009] S3, mixing the fine powder and the pore-forming agent 2 to obtain a mixture;
[0010] S4, subjecting the mixed material to a first high-temperature carbonization to obtain a first composite material with a porous surface;
[0011] S5, adding a metal salt solution having a catalytic effect of generating CNTs to the first composite material having a porous surface, and performing a drying treatment to obtain a dried material;
[0012] S6. In an inert atmosphere, a carbon source is deposited on the dried material by a high temperature vapor deposition method to obtain a second composite material;
[0013] S7, subjecting the second composite material to a second high-temperature carbonization to obtain a third composite material;
[0014] S8, purifying, filtering, washing and drying the third composite material to obtain a purified material;
[0015] S9. Use a coating agent to coat the purified material to obtain a graded-pore sodium electric hard carbon negative electrode material.
[0016] Compared with the prior art, in the present invention, in step S1, the hard carbon precursor material is mixed with the pore former 1 and subjected to low-temperature pre-carbonization, which can form a large number of mesoporous structures inside the hard carbon material, increase the specific surface area of the material, and facilitate the storage and transmission of sodium ions. The pore former 2 is added in S3 to occupy the pore structure exposed to the outside of the fine powder, so that the pore structure is retained after the first high-temperature carbonization in S4, and finally the pore former 1 and the pore former 2 are washed away in the purification of S8 to obtain a material rich in mesoporous and microporous structures. In addition, the metal salt solution with the effect of catalyzing CNT generation added in S5 acts as a catalyst in the high-temperature vapor deposition process of S6 to promote the decomposition of carbon-containing gas, thereby forming carbon nanotubes (CNTs) with excellent electronic conductivity on the surface and inside of the hard carbon material. The carbon nanotubes themselves have a one-dimensional tubular structure, with a large cavity inside and a rich surface outside. These structural characteristics provide additional transmission paths for sodium ions. Therefore, the present application prepares a hierarchical porous sodium electric hard carbon negative electrode material with micropores, mesopores, and carbon nanotube structures, so that sodium ions can not only migrate along the mesopores and micropores in the hard carbon material, but also be transmitted through the inner and outer surfaces of the carbon nanotubes, which can significantly optimize the ion transmission path and electronic conduction, thereby improving the rate performance of the sodium ion battery. In addition, in S9, the purified material is coated with a coating agent, and the coating layer can reduce the direct contact between the hard carbon material and the electrolyte, reduce the occurrence of side reactions, and further improve the first efficiency and rate performance of the sodium ion battery. In summary, the hierarchical porous sodium electric hard carbon negative electrode material obtained by the preparation method of the present application has micropores, mesopores, carbon nanotubes and coating layer structures, which can optimize the ion transmission path and electronic conduction and reduce the occurrence of side reactions, thereby significantly improving the first efficiency and rate performance of the sodium ion battery.
[0017] As an embodiment, the hard carbon precursor material is selected from at least one of phenolic resin, polyacrylonitrile, polystyrene, polyfurfural, and polyfuran resin. Preferably, the hard carbon precursor is selected from coconut shell.
[0018] As one embodiment, the pore former 1 is selected from at least one of NaCl, NaOH, KOH, ZnCl2, and Na2CO3. Preferably, the pore former 1 is selected from NaCl.
[0019] As one embodiment, the pore former 2 is selected from at least one of NaOH, KOH, and ZnCl 2. Preferably, the pore former 2 is selected from ZnCl 2.
[0020] As an embodiment, the metal salt solution having the effect of catalyzing the formation of CNTs is selected from chloride or nitrate of metal M, and metal M is iron, cobalt or nickel.
[0021] As an embodiment, the temperature of low-temperature pre-carbonization in S1 is 350°C to 650°C, and the time is 0.5h to 10h. Specifically, the temperature of low-temperature pre-carbonization may be, but not limited to, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C, 510°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 630°C, 650°C; the time may be, but not limited to, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h.
[0022] As one implementation scheme, the mass of the pore former 1 in S1 accounts for 0.1% to 10% of the mass of the hard carbon precursor material; by way of example, the mass of the pore former 1 accounts for 0.1%, 0.7%, 1.2%, 1.5%, 1.8%, 3%, 3.5%, 4.5%, 5%, 5.5%, 6.5%, 7.5%, 8.5%, 10% of the mass of the hard carbon precursor material, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0023] As an implementation scheme, the pulverization in S2 includes: first performing double-roll crushing and then using air flow crushing; specifically, first using a double-roll device to roll-crush the first composite material to 2 mm, and then using an air flow crusher to crush.
[0024] As one embodiment, the fine powder in S2 has a Dv10 of 2 μm to 4 μm, a Dv50 of 4 to 8 μm, a Dv90 of 8 to 14 μm, a Dv99 of 45 μm or less, and a value of (Dv90-Dv10) / Dv50 of 1.2 to 1.5.
[0025] As one implementation scheme, the mass of the pore former 2 in S3 accounts for 0.1% to 10% of the mass of the hard carbon precursor material; by way of example, the mass of the pore former 2 accounts for 0.1%, 0.7%, 1.2%, 1.5%, 1.8%, 3%, 3.5%, 4.5%, 5%, 5.5%, 6.5%, 7.5%, 8.5%, 10% of the mass of the hard carbon precursor material, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0026] As one embodiment, the mass of the metal salt having a catalytic CNT generation effect in S5 accounts for 0.1% to 5% of the mass of the hard carbon precursor material; as an example, the mass of the metal salt having a catalytic CNT generation effect accounts for 0.1%, 0.7%, 1.2%, 1.5%, 1.8%, 3%, 3.5%, 4.5%, and 5% of the mass of the hard carbon precursor material, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] As an implementation scheme, the drying temperature in S5 is ≥80°C, and the drying time is ≥2h; for example, the drying temperature may be, but not limited to, 80°C, 83°C, 86°C, 88°C, 90°C, 93°C, 97°C, 100°C, 102°C, 105°C, 108°C, and 110°C; the drying time may be, but not limited to, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h, 10.0h, 10.5h, 11.0h, 11.5h, and 12.0h. The drying process can remove moisture from the hard carbon material, ensuring that the material will not react adversely due to the presence of moisture in the subsequent high-temperature vapor deposition method.
[0028] As one embodiment, the gas of the inert atmosphere in S6 is selected from at least one of nitrogen and argon; preferably, the gas of the inert atmosphere is selected from nitrogen.
[0029] As an embodiment, the carbon source in S6 is at least one of methane, acetylene and ethylene. Preferably, the carbon source is acetylene.
[0030] As an implementation scheme, the temperature of the high temperature vapor deposition method in S6 is 700°C to 1000°C, and the time is 0.5h to 5h; the temperature of the high temperature vapor deposition method may be, but not limited to, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C; the time may be, but not limited to, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h. Specifically, the high temperature vapor deposition method is carried out in a CVD furnace, and the heating rate is 3 to 6°C / min, preferably, the heating rate is 5°C / min.
[0031] As an implementation scheme, the temperature of the second high-temperature carbonization in S7 is 1100°C to 1600°C, and the time is 0.5h to 10h; the temperature of the high-temperature carbonization may be, but is not limited to, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C; the time may be, but is not limited to, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h, 10.0h. Step S7 can further stabilize the structure of the hard carbon material and improve the electrochemical performance.
[0032] As an embodiment, the purification in S8 includes soaking the third composite material with an acid; for example, the acid may be but is not limited to at least one of hydrochloric acid, hydrofluoric acid, and nitric acid; and the filtering and washing includes controlling the pH of the filtrate after filtering and washing to be ≥6.5.
[0033] As one implementation scheme, the drying temperature in S8 is ≥80°C, and the time is ≥2h; the drying temperature may be, but is not limited to, 80°C, 83°C, 86°C, 89°C, 93°C, 96°C, 98°C, 100°C, 103°C, 106°C, 108°C, 110°C; the drying time may be, but is not limited to, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h.
[0034] As an implementation scheme, the ash content of the purified material in S8 is ≤0.5%. Step S8 can remove impurities and moisture that may exist in the material to ensure the purity of the material, which is very important for improving the electrochemical stability of the material.
[0035] As one embodiment, the coating agent in S9 is selected from at least one of asphalt, resin, and starch; preferably, the coating agent is selected from phenolic resin.
[0036] As one implementation scheme, the coating temperature in S9 is 1000°C to 1600°C, and the holding time is 0.5h to 10h; the coating temperature may specifically be but not limited to 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C; the holding time may specifically be but not limited to 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 9.0h, 9.5h, 10.0h.
[0037] As one implementation scheme, the graded pore sodium electric hard carbon negative electrode material Dv10 in S9 is 1 μm to 3 μm, Dv50 is 3 to 7 μm, Dv90 is 7 to 13 μm, Dv99 is below 40 μm, and the value of (Dv90-Dv10) / Dv50 is 1.4 to 2.0.
[0038] Correspondingly, the second aspect of the present invention further provides a hierarchical porosity sodium electric hard carbon negative electrode material, which is prepared by the above-mentioned method for preparing the hierarchical porosity sodium electric hard carbon negative electrode material. DETAILED DESCRIPTION
[0039] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with the embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a graded-porous sodium electric hard carbon negative electrode material, the steps comprising:
[0042] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0043] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0044] S3, add the fine powder and 104g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0045] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0046] S5, adding 42 g of ferric chloride solution having a catalytic effect on CNT generation to the first surface porous composite material, and then drying it in a blast drying oven at 110° C. for 6 h to obtain 1544 g of dried material;
[0047] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1440g of the second composite material;
[0048] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1332g of the third composite material;
[0049] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 549g of purified material;
[0050] S9. Put the purified material into a beaker, add 216g of phenolic resin solution with a concentration of 60% diluted with alcohol and stir to mix. After mixing, put it into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, and the nitrogen flow rate is 1L / min. Adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h. After cooling, take out the graphite crucible to obtain 727g of graded porous sodium electric hard carbon negative electrode material.
[0051] Example 2
[0052] This embodiment provides a method for preparing a graded-porous sodium electric hard carbon negative electrode material, the steps comprising:
[0053] S1, 5.0kg coconut shell particles and 250gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min and the material was incubated at 600°C for 2.3h, the graphite crucible was taken out after cooling, and 1650g of the first composite material was obtained;
[0054] S2, using a roller device to roll the first composite material to crush it to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1320g of fine powder;
[0055] S3, add the fine powder and 52g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0056] S4, subjecting the mixed material to heat treatment at 900° C. for 0.6 h to obtain a first composite material with a porous surface;
[0057] S5, adding 21 g of ferric chloride solution having a catalytic effect on CNT generation to the first surface porous composite material, and then drying it in a blast drying oven at 100° C. for 8 h to obtain 1366 g of dried material;
[0058] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 1000°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1216g of the second composite material;
[0059] S7, the second composite material is placed in a graphite crucible, the graphite crucible is placed in a high temperature atmosphere furnace, the furnace atmosphere is adjusted to nitrogen, the nitrogen flow rate is 1L / min, the heating rate is adjusted to 5°C / min so that the material is kept at 1500°C for 3.5h, the graphite crucible is taken out after cooling, and 1194g of the third composite material is obtained;
[0060] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven for drying at 100°C for 4h to obtain 456g of purified material;
[0061] S9. Put the purified material into a beaker, add 144g of phenolic resin solution with a concentration of 60% diluted with alcohol and stir to mix. After mixing, put it into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, and the nitrogen flow rate is 1L / min. Adjust the heating rate to 5℃ / min so that the material is kept warm at 1500℃ for 3.5h. After cooling, take out the graphite crucible to obtain 599g of graded porous sodium electric hard carbon negative electrode material.
[0062] Example 3
[0063] This embodiment provides a method for preparing a graded-porous sodium electric hard carbon negative electrode material, the steps comprising:
[0064] S1, 5.0kg coconut shell particles and 700gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 450°C for 4.5h, the graphite crucible was taken out after cooling, and 2450g of the first composite material was obtained;
[0065] S2, using a roller device to roll the first composite material to crush it to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1760g of fine powder;
[0066] S3, add the fine powder and 156g NaOH crystals into a beaker, then pour in 2L deionized water and stir to mix well to obtain a mixture;
[0067] S4, subjecting the mixed material to heat treatment at 760° C. for 2 h to obtain a first composite material with a porous surface;
[0068] S5, adding 63 g of nickel chloride solution having a catalytic effect on CNT generation to the first surface porous composite material, and then drying it in a forced air drying oven at 80° C. for 12 h to obtain 1740 g of dried material;
[0069] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 1100°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept at 2.5h. After cooling, the material was taken out to obtain 1601g of the second composite material;
[0070] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1400°C for 5h, taking out the graphite crucible after cooling, and obtaining 1608g of the third composite material;
[0071] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 85°C for 6h to obtain 486g of purified material;
[0072] S9. Put the purified material into a beaker, add 288g of phenolic resin solution with a concentration of 60% diluted with alcohol and stir to mix. After mixing, put it into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, and the nitrogen flow rate is 1L / min. Adjust the heating rate to 5℃ / min so that the material is kept warm at 1300℃ for 5.5h. After cooling, take out the graphite crucible to obtain 759g of graded porous sodium electric hard carbon negative electrode material.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that: S9 of this embodiment is: put the purified material into a beaker, add 72g of phenolic resin solution with a concentration of 60% diluted with alcohol, stir and mix, put it into a graphite crucible after mixing, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min, keep the material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 590g of graded porous sodium electric hard carbon negative electrode material;
[0075] The rest is exactly the same as in Example 1.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 1 is that: S9 of this embodiment is: put the purified material into a beaker, add 144g of phenolic resin solution with a concentration of 60% diluted with alcohol, stir and mix, put it into a graphite crucible after mixing, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min, keep the material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 658g of graded porous sodium electric hard carbon negative electrode material;
[0078] The rest is exactly the same as in Example 1.
[0079] Example 6
[0080] The difference between this embodiment and embodiment 1 is that: S9 of this embodiment is: put the purified material into a beaker, add 288g of phenolic resin solution with a concentration of 60% diluted with alcohol, stir and mix, put it into a graphite crucible after mixing, put the graphite crucible into a high-temperature atmosphere furnace, adjust the atmosphere in the furnace to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 795g of graded porous sodium electric hard carbon negative electrode material;
[0081] The rest is exactly the same as in Example 1.
[0082] Comparative Example 1
[0083] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0084] S1, pour 5kg coconut shell particles into a graphite crucible, put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5°C / min to keep the material at 500°C for 2h, take out the graphite crucible after cooling, and obtain 1500g of the first composite material;
[0085] S2, using a double-roll device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1200g of fine powder;
[0086] S3, add the fine powder into a beaker, and then pour in 2L of deionized water and stir to mix evenly to obtain a mixture;
[0087] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0088] S5, drying the first composite material with porous surface in a forced air drying oven at 110° C. for 6 h to obtain 1080 g of dried material;
[0089] S6, put the dried material into a CVD furnace, adjust the protective atmosphere in the furnace to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5°C / min so that the material is kept at 850°C for 3h, take out the material after cooling, and obtain 864g of the second composite material;
[0090] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 778g of the third composite material;
[0091] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven for drying at 110°C for 3h to obtain 622g of purified material;
[0092] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 591g of graded porous sodium electric hard carbon negative electrode material.
[0093] Comparative Example 2
[0094] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0095] S1, 5kg coconut shell particles and 250gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min and the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 1750g of the first composite material was obtained;
[0096] S2, using a double-roll device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1400g of fine powder;
[0097] S3, add the fine powder into a beaker, and then pour in 2L of deionized water and stir to mix evenly to obtain a mixture;
[0098] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0099] S5, drying the first composite material with porous surface in a forced air drying oven at 110° C. for 6 h to obtain 1260 g of dried material;
[0100] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1058g of the second composite material;
[0101] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 977g of the third composite material;
[0102] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 582g of purified material;
[0103] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 553g of graded porous sodium electric hard carbon negative electrode material.
[0104] Comparative Example 3
[0105] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0106] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0107] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0108] S3, add the fine powder into a beaker, and then pour in 2L of deionized water and stir to mix evenly to obtain a mixture;
[0109] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0110] S5, drying the first composite material with porous surface in a forced air drying oven at 110° C. for 6 h to obtain 1440 g of dried material;
[0111] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1252g of the second composite material;
[0112] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1177g of the third composite material;
[0113] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 541g of purified material;
[0114] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 514g of graded porous sodium electric hard carbon negative electrode material.
[0115] Comparative Example 4
[0116] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0117] S1, 5kg coconut shell particles and 750gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min and the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2250g of the first composite material was obtained;
[0118] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0119] S3, add the fine powder into a beaker, and then pour in 2L of deionized water and stir to mix evenly to obtain a mixture;
[0120] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0121] S5, drying the first composite material with porous surface in a forced air drying oven at 110° C. for 6 h to obtain 1620 g of dried material;
[0122] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1446g of the second composite material;
[0123] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1376g of the third composite material;
[0124] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 501g of purified material;
[0125] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 476g of graded porous sodium electric hard carbon negative electrode material.
[0126] Comparative Example 5
[0127] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0128] S1, 5kg coconut shell particles and 1000gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2500g of the first composite material was obtained;
[0129] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0130] S3, add the fine powder into a beaker, and then pour in 2L of deionized water and stir to mix evenly to obtain a mixture;
[0131] S4, subjecting the mixed material to heat treatment at 800° C. for 1 h to obtain a first composite material with a porous surface;
[0132] S5, drying the first composite material with porous surface in a forced air drying oven at 110° C. for 6 h to obtain 1800 g of dried material;
[0133] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1640g of the second composite material;
[0134] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1576g of the third composite material;
[0135] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 461g of purified material;
[0136] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 438g of graded porous sodium electric hard carbon negative electrode material.
[0137] Comparative Example 6
[0138] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0139] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0140] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0141] S3, add the fine powder and 52g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0142] S4, subjecting the mixed material to heat treatment at 900° C. for 0.6 h to obtain a first composite material with a porous surface;
[0143] S5, adding 21g of ferric chloride solution having a catalytic effect on CNTs to the first surface porous composite material, and then drying it in a blast drying oven at 110°C for 6h to obtain 1492g of dried material;
[0144] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1346g of the second composite material;
[0145] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1254g of the third composite material;
[0146] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven for drying at 110°C for 3h to obtain 545g of purified material;
[0147] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 518g of graded porous sodium electric hard carbon negative electrode material.
[0148] Comparative Example 7
[0149] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0150] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0151] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0152] S3, add the fine powder and 104g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0153] S4, subjecting the mixed material to heat treatment at 900° C. for 0.6 h to obtain a first composite material with a porous surface;
[0154] S5, adding 42g of ferric chloride solution having a catalytic effect on CNTs to the first surface porous composite material, and then drying it in a blast drying oven at 110°C for 6h to obtain 1544g of dried material;
[0155] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1440g of the second composite material;
[0156] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1332g of the third composite material;
[0157] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 549g of purified material;
[0158] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 521g of graded porous sodium electric hard carbon negative electrode material.
[0159] Comparative Example 8
[0160] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0161] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0162] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0163] S3, add the fine powder and 156g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0164] S4, subjecting the mixed material to heat treatment at 900° C. for 0.6 h to obtain a first composite material with a porous surface;
[0165] S5, adding 63g of ferric chloride solution having a catalytic effect on CNT to the first surface porous composite material, and then drying it in a blast drying oven at 110°C for 6h to obtain 1596g of dried material;
[0166] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1534g of the second composite material;
[0167] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1409g of the third composite material;
[0168] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven and drying it at 110°C for 3h to obtain 552g of purified material;
[0169] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 525g of graded porous sodium electric hard carbon negative electrode material.
[0170] Comparative Example 9
[0171] This comparative example provides a method for preparing a graded-pore sodium electric hard carbon negative electrode material, the steps comprising:
[0172] S1, 5kg coconut shell particles and 500gNaCl were mixed in a VC mixer and poured into a graphite crucible, the graphite crucible was placed in a box furnace, the furnace was adjusted to a nitrogen atmosphere, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min, the material was incubated at 500°C for 2h, the graphite crucible was taken out after cooling, and 2000g of the first composite material was obtained;
[0173] S2, using a roller device to roll the first composite material to 2mm, and then using a jet mill to crush it to a discharge particle size Dv10 controlled at 2μm, a particle size Dv50 controlled at 5μm, a particle size Dv90 controlled at 10μm, a particle size Dv99 controlled at 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 value of 1.6, to obtain 1600g of fine powder;
[0174] S3, add the fine powder and 208g ZnCl2 crystals into a beaker, and then pour in 2L deionized water to stir and mix well to obtain a mixture;
[0175] S4, subjecting the mixed material to heat treatment at 900° C. for 0.6 h to obtain a first composite material with a porous surface;
[0176] S5, adding 84 g of ferric chloride solution having a catalytic effect on CNTs to the first surface porous composite material, and then drying it in a blast drying oven at 110° C. for 6 h to obtain 1648 g of dried material;
[0177] S6, the dried material was placed in a CVD furnace, the protective atmosphere in the furnace was adjusted to nitrogen, the nitrogen flow rate was 1L / min, the heating rate was adjusted to 5°C / min so that the material was under the condition of 850°C, and then the carbon-containing gas was adjusted to acetylene, the acetylene flow rate was 3L / min, and the temperature was kept for 3h. After cooling, the material was taken out to obtain 1628g of the second composite material;
[0178] S7, putting the second composite material into a graphite crucible, putting the graphite crucible into a high-temperature atmosphere furnace, adjusting the furnace atmosphere to nitrogen, the nitrogen flow rate to 1L / min, adjusting the heating rate to 5°C / min so that the material is kept warm at 1600°C for 2h, taking out the graphite crucible after cooling, and obtaining 1487g of the third composite material;
[0179] S8, placing the third composite material in a beaker, adding 160g of hydrochloric acid for acid soaking, and filtering and washing the third composite material using a positive pressure filter after acid soaking for 3h until the pH of the washing filtrate is 7, and then placing the third composite material in a blast drying oven for drying at 110°C for 3h to obtain 556g of purified material;
[0180] S9. Put the purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace atmosphere to nitrogen, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min so that the material is kept warm at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain 528g of graded porous sodium electric hard carbon negative electrode material.
[0181] The particle size of the graded porous sodium electric hard carbon negative electrode materials of Examples 1 to 6 and Comparative Examples 1 to 9 was tested using the Malvern laser particle size analyzer MS2000; the specific surface area of the graded porous sodium electric hard carbon negative electrode materials of Examples 1 to 6 and Comparative Examples 1 to 9 was tested using the Kantar specific surface area measurement NOVA2000e; the test results are shown in Table 1.
[0182] The hierarchical pore sodium electric hard carbon negative electrode materials of Examples 1 to 6 and Comparative Examples 1 to 9 are applied to a half-cell according to the following method:
[0183] The graded porous sodium electric hard carbon negative electrode material, SBR, CMC, and conductive SP were mixed evenly in a mass ratio of 95:2.5:1.5:1, and coated on aluminum foil. The coated electrode was placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours for use, and then punched into small discs with a diameter of 14 mm. Then it was transferred to a German Mikaelona glove box filled with argon gas to assemble into a 2430-type button battery, with a three-component mixed solvent of 1 mol / L NaClO4 in a mixture of EC:PC (1:1) + 5% FEC (volume ratio) as the electrolyte, a metal sodium sheet as the counter electrode, and a 16μm thick U-shaped diaphragm as the isolation membrane to form a half-cell.
[0184] The electrochemical performance of the assembled half-cell was tested on the Arbin electrochemical detection system in the United States: First, the battery was subjected to 3 cycles of 0.2C formation to ensure that the electrode material was fully activated and a stable SEI film was formed. Then, the charge and discharge test was performed at a rate of 0.5C, and the gram capacity and initial efficiency were recorded; then the charge and discharge test was performed at a rate of 1.0C, and the discharge capacity was also recorded, and the capacity ratio was calculated, which was the ratio of 1.0C discharge capacity / gram capacity × 100%. The test results are shown in Table 1.
[0185] Table 1
[0186]
[0187]
[0188]
[0189] By comparing comparative examples 1 to 5, it can be seen that an increase in the proportion of pore-forming agent 1 will lead to an increase in the number of pore structures in the hard carbon material. More pore structures significantly increase the specific surface area of the material, and the increase in specific surface area helps to improve the electrochemical properties of the material, especially its capacity performance.
[0190] It can be seen from the comparative analysis of Examples 6 to 9 that adjusting the content of the pore former 2 in step S3 and the content of the metal salt solution with catalytic effect in step S5 will affect the specific surface area of the material, which shows that the introduction of micropores and carbon nanotubes has a significant effect on the total specific surface area. As the specific surface area increases, the capacity of the material is improved, but at the same time, the initial efficiency will decrease.
[0191] By comparing Comparative Examples 6 to 9 with Examples 1 and Examples 4 to 6, it can be seen that adjusting the content of the coating agent will also affect the specific surface area of the material. After coating, the specific surface area of the graded porous sodium electric hard carbon negative electrode material can be reduced to 2 to 4 m 2 / g, and the capacity of the material not only did not decrease, but increased slightly, and the first efficiency was also improved.
[0192] In summary, the hierarchical pore sodium electric hard carbon negative electrode material prepared by the preparation method of the present application can significantly improve the first efficiency and rate performance of sodium ion batteries. This is because the hierarchical pore sodium electric hard carbon negative electrode material prepared in the present application has a structure of micropores, mesopores, carbon nanotubes and coating layers, so that sodium ions can not only migrate along the mesopores and micropores in the hard carbon material, but also be transmitted through the inner and outer surfaces of the carbon nanotubes, which can significantly optimize the ion transmission path and electronic conduction, thereby improving the rate performance of the sodium ion battery. In addition, the coating layer can reduce the direct contact between the hard carbon material and the electrolyte, reduce the occurrence of side reactions, and further improve the first efficiency and rate performance of the sodium ion battery.
[0193] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a hierarchical pore sodium electric hard carbon negative electrode material, characterized in that the steps include: S1, mixing a hard carbon precursor material and a pore-forming agent 1 and then pre-carbonizing at a low temperature to obtain a first composite material; S2, crushing the first composite material to obtain a fine powder; S3, stirring and mixing the fine powder and pore-forming agent 2 to obtain a mixed material; S4, subjecting the mixed material to a first high-temperature carbonization to obtain a first composite material with a porous surface; S5, adding a metal salt solution having a catalytic effect of generating CNTs to the first surface porous composite material, and performing drying treatment to obtain a dried material; S6. In an inert atmosphere, using a high temperature vapor deposition method to deposit a carbon source on the dried material to obtain a second composite material; S7, subjecting the second composite material to a second high-temperature carbonization to obtain a third composite material; S8, purifying, filtering, washing and drying the third composite material to obtain a purified material; S9, coating the purified material with a coating agent to obtain a graded-pore sodium electric hard carbon negative electrode material.
2. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The hard carbon precursor material is selected from at least one of phenolic resin, polyacrylonitrile, polystyrene, polyfurfural and polyfuran resin.
3. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The pore-forming agent 1 is selected from at least one of NaCl, NaOH, KOH, ZnCl2, and Na2CO3.
4. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The pore former 2 is selected from at least one of NaOH, KOH and ZnCl2.
5. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The metal salt solution having the effect of catalyzing the formation of CNTs is selected from chloride or nitrate of metal M, and the metal M is iron, cobalt or nickel.
6. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The temperature of the low-temperature pre-carbonization in S1 is 350° C. to 650° C., and the time is 0.5 h to 10 h.
7. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The carbon source in S6 is at least one of methane, acetylene and ethylene.
8. The method for preparing the hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The graded pore sodium electric hard carbon negative electrode material described in S9 has a Dv10 of 1 μm to 3 μm, a Dv50 of 3 to 7 μm, a Dv90 of 7 to 13 μm, a Dv99 of less than 40 μm, and a value of (Dv90-Dv10) / Dv50 of 1.4 to 2.
0.
9. The method for preparing a hierarchical pore sodium electric hard carbon negative electrode material according to claim 1, characterized in that: The invention comprises at least one of the following features (1) to (14): (1) The mass of the pore former 1 in S1 accounts for 0.1% to 10% of the mass of the hard carbon precursor material; (2) The pulverization in S2 includes: firstly performing roller crushing and then using air flow crushing; (3) The fine powder in S2 has a Dv10 of 2 μm to 4 μm, a Dv50 of 4 to 8 μm, a Dv90 of 8 to 14 μm, a Dv99 of 45 μm or less, and a value of (Dv90-Dv10) / Dv50 of 1.2 to 1.5; (4) The mass of the pore former 2 in S3 accounts for 0.1% to 10% of the mass of the hard carbon precursor material; (5) The temperature of the first high temperature carbonization in S4 is 700° C. to 900° C., and the time is 0.5 h to 5 h; (6) The mass of the metal salt having a catalytic effect on CNT formation described in S5 accounts for 0.1% to 5% of the mass of the hard carbon precursor material; (7) The drying temperature in S5 is ≥80°C and the drying time is ≥2h; (8) The inert atmosphere gas in S6 is selected from at least one of nitrogen and argon; (9) The temperature of the high temperature vapor deposition method in S6 is 700°C to 1000°C, and the time is 0.5h to 5h; (10) The temperature of the second high temperature carbonization in S7 is 1100° C. to 1600° C., and the time is 0.5 h to 10 h; (11) The purification in S8 includes soaking the third composite material in an acid; the drying temperature is ≥80°C and the drying time is ≥2h; (12) The ash content of the purified material in S8 is ≤ 0.5%; (13) The coating agent in S9 is selected from at least one of asphalt, resin, and starch; (14) The coating temperature in S9 is 1000°C to 1600°C, and the insulation time is 0.5h to 10h.
10. A hierarchical pore sodium electric hard carbon negative electrode material, characterized in that: The material is prepared by the method for preparing the graded-pore sodium electric hard carbon negative electrode material as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Porous hard carbon negative electrode material, preparation method thereof and lithium ion battery
CN108963253A
Porous hard carbon material as well as preparation method and application thereof
CN113735095A
Preparation method of sodium ion battery negative electrode hard carbon material with closed microporous structure
CN117003237A
Preparation method and application of hierarchical pore hard carbon material
CN117069097A
Graded porous carbon as well as preparation method and application thereof
CN118016879A